Prevention of Obesity in The Elderly Through Health Promotion Interventions: Literature Review - Miranda Gracia Salsabila; Ernawaty Ernawaty; Indah Berliana Fauziah (Preventia : The Indonesian Journal of Public Health, 2024)
The incidence of obesity among the elderly is rising in many countries, including Indonesia. To address this issue, effective interventions are necessary to change lifestyle and dietary habits, such as through social marketing and health promotion initiatives for the elderly. Preventing obesity in this demographic through social marketing can involve educational campaigns, intervention programs, community empowerment, and collaboration with various stakeholders. This study aims to identify strategies to prevent obesity in the elderly through health promotion interventions. The study is a literature review following the PRISMA 2009 protocol. Articles were sourced from Google Scholar, ScienceDirect, and PubMed databases, focusing on those published in the last five years (2019 until 2024) and discussing obesity in the elderly. The search used keywords like "obesity," "elderly," "prevention," and "health promotion" with Boolean operators. Out of 98,447 articles found, only 8 met the inclusion criteria and were selected for further analysis. The review concluded that increasing awareness and preventing obesity in the elderly can be achieved through educational methods using various media, including print and audiovisual aids (AVA), health education, and regular check-ups.